Uwagi o kształtowaniu świadomości prawnej w procesie edukacyjnym w szkołach podstawowych i ponadpodstawowych - Łukawska-Białogłowska, Dominika (PRAWO i WIĘŹ, 2025)
From November 2022 till June 2024 on the Faculty of Law and Administration of the University of Łódź was implemented project no. B2211900001254000 entitled “What’s New in the Law?”, co-financed by the Ministry of Education and Science (currently: the Ministry of Science and Higher Education) under contract no. SONP/SP/548436/2022 as part of the “Social Responsibility of Science” program. It consisted of conducting classes on the basics of law in 25 schools in the Łódź Province (primary and secondary schools) for a total of 5,482 students. During classes at schools, participants confronted their current knowledge of legal issues with information and cases prepared by the course instructors (Dominika Łukawska-Białogłowska, PhD and Ewa Urbaniak, PhD), and were also encouraged to present their comments and thoughts, including in the form of surveys and conversations, while during meetings at the seat of the Faculty of Law and Administration of the University of Łódź, they took part in simulations of court hearings. The project drew attention to the need to consider changes in the way school students are educated in the field of legal knowledge. The subject of this paper is consideration of the proposed solutions that would contribute – In the author’s opinion – to the development of legal awareness among children and young people.